Desmin common mutation is associated with multi-systemic disease manifestations and depletion of mitochondria and mitochondrial DNA - McCormick, Elizabeth M.; Kenyon, Lawrence; Falk, Marni J. (Frontiers in Genetics, 2015)
Desmin (DES) is a major muscle scaffolding protein that also functions to anchor mitochondria. Pathogenic DES mutations, however, have not previously been recognized as a cause of multi-systemic mitochondrial disease. Here, we describe a 45-year-old man who presented to The Children’s Hospital of Philadelphia Mitochondrial-Genetics Diagnostic Clinic for evaluation of progressive cardiac, neuromuscular, gastrointestinal, and mood disorders. Muscle biopsy at age 45 was remarkable for cytoplasmic bodies, as well as ragged red fibers and SDH positive/COX negative fibers that were suggestive of a mitochondrial myopathy. Muscle also showed significant reductions in mitochondrial content (16% of control mean for citrate synthase activity) and mitochondrial DNA (35% of control mean). His family history was significant for cardiac conduction defects and myopathy in multiple maternal relatives. Multiple single gene and panel-based sequencing studies were unrevealing. Whole exome sequencing identified a known pathogenic p.S13F mutation in DES that had previously been associated with desmin-related myopathy. Desmin-related myopathy is an autosomal dominant disorder characterized by right ventricular hypertrophic cardiomyopathy, myopathy, and arrhythmias. However, neuropathy, gastrointestinal dysfunction, and depletion of both mitochondria and mitochondrial DNA have not previously been widely recognized in this disorder. Recognition that mitochondrial dysfunction occurs in desmin-related myopathy clarifies the basis for the multi-systemic manifestations, as are typical of primary mitochondrial disorders. Understanding the mitochondrial pathophysiology of desmin-related myopathy highlights the possibility of new therapies for the otherwise untreatable and often fatal class of disease. We postulate that drug treatments aimed at improving mitochondrial biogenesis or reducing oxidative stress may be effective therapies to ameliorate the effects of desmin-related disease.